2006
DOI: 10.1161/01.atv.0000229658.76797.30
|View full text |Cite
|
Sign up to set email alerts
|

Flow Effects on Coagulation and Thrombosis

Abstract: Abstract-Thrombosis occurs in a dynamic rheological field that constantly changes as the thrombus grows to occlusive dimensions. In the initiation of thrombosis, flow conditions near the vessel wall regulate how quickly reactive components are delivered to the injured site and how rapidly the reaction products are disseminated. Whereas the delivery and removal of soluble coagulation factors to the vessel is thought to occur via classic convection-diffusion phenomena, the movement of cells and platelets to the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
296
1
2

Year Published

2007
2007
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 348 publications
(307 citation statements)
references
References 95 publications
8
296
1
2
Order By: Relevance
“…Current ÔflowÕ models examining how the processes of coagulation and thrombosis come together are limited, and investigating the dynamic ÔflowÕ environment continues to remain a challenge [28].…”
Section: Discussionmentioning
confidence: 99%
“…Current ÔflowÕ models examining how the processes of coagulation and thrombosis come together are limited, and investigating the dynamic ÔflowÕ environment continues to remain a challenge [28].…”
Section: Discussionmentioning
confidence: 99%
“…Intravascular thrombosis is another compelling pathology associated with most cardiovascular diseases where near-wall transport becomes important [7,25]. The trajectories of individual platelets and the accumulation and residence time of chemical solutes including ADP, thrombin, and various blood factors control clot formation.…”
Section: Introductionmentioning
confidence: 99%
“…The local transport of several substances near and at the vessel wall are known to influence atherosclerosis progression [56]. For example, previous studies have looked into transport of low density lipoproteins (LDL) [17,20,30,14], high density lipoproteins (HDL) [40,24], oxygen [16,27], nitric oxide (NO) [45,35], monocytes [12,14], and adenine triphosphate ATP and adenine diphosphate ADP [13,15,8] as important mass transport processes involved in atherosclerosis.Intravascular thrombosis is another compelling pathology associated with most cardiovascular diseases where near-wall transport becomes important [7,25]. The trajectories of individual platelets and the accumulation and residence time of chemical solutes including ADP, thrombin, and various blood factors control clot formation.…”
mentioning
confidence: 99%
“…It was observed that the infusion of Tan IIA induced a decrease in PT and APTT when compared to the LPS control group. Platelet aggregation is one of the important triggers of blood coagulation in the pathologic thrombosis associated with DIC [15] . DIC produces massive thrombin, stimulates platelet aggregation and triggers the blood coagulation cascades.…”
Section: Discussionmentioning
confidence: 99%